2014
DOI: 10.3748/wjg.v20.i21.6374
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriinfection and inflammatory bowel disease: Is there a link?

Abstract: Helicobacter pylori (H. pylori) infection is one of the most widely spread infectious diseases in humans. It can cause chronic gastritis, peptic ulcer disease and gastric malignancies and has been associated with extra-gastric disorders. H. pylori elicit a chronic systemic inflammatory response which, under certain conditions, may trigger autoimmune reactions and may be implicated in the pathogenesis of autoimmune diseases. Although the pathogenesis of inflammatory bowel disease (IBD) is unknown, it is thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 0 publications
2
91
1
8
Order By: Relevance
“…A role for Helicobacter species in IBD has also been proposed (Papamichael et al, 2014) (Table 2). However, findings are varied and, to date, have failed to support a definitive association in IBD (Hold et al, 2014).…”
Section: Helicobacter Speciesmentioning
confidence: 99%
“…A role for Helicobacter species in IBD has also been proposed (Papamichael et al, 2014) (Table 2). However, findings are varied and, to date, have failed to support a definitive association in IBD (Hold et al, 2014).…”
Section: Helicobacter Speciesmentioning
confidence: 99%
“…Case reports and epidemiological studies have observed that IBD may appear quickly after HP eradication, possibly due to a shift in the Th pattern. However, other studies have exposed that this lower preva-lence of HP in IBD might be secondary to HP "spontaneous eradication" with 5-ASA or antibiotic treatment [65] . Other Helicobacter species, like Helicobacter hepaticus, have shown their capability of inducing colitis in animals, mainly in immunocompromised ones.…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…So far, conflicting results about the role of infectious diseases in the pathogenesis and severity of several rheumatic diseases were reported in the literature [8][9][10][11]17]. H. pylori was investigated whether it is related with several autoimmune diseases or not and it was found to be associated with development and severity of Sjögren's syndrome, Systemic sclerosis and Psoriasis while no relation was found with RA, Systemic lupus erythematosus, vasculitides, chronic urticaria, Immune thrombocytopenic purpura and Hashimoto's thyroiditis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) infection was also found to reveal a number of host immune responses which results in chronic inflammation [9]. The protective role of H. pylori infection on some autoimmune chronic inflammatory diseases such as inflammatory bowel disease was also reported [10]. Besides, H. pylori infection was found to take part in the pathogenesis of Rheumatoid arthritis (RA) [11].…”
mentioning
confidence: 99%